Arterial hypertension in children and adolescents - Kawałko, Kinga; Rynio, Grzegorz; Dubiel, Magdalena; Ziojła, Kinga; Książek, Anna; Sufin, Patrycja; Masłocha, Aleksander (Journal of Education, Health and Sport, 2022)
Arterial hypertension is a serious clinical problem in everyday medical practice. It mainly affects adult patients, but is also increasingly common in children and adolescents. Making a diagnosis is possible thanks to systematic measurements of blood pressure during routine medical visits, while maintaining appropriate rules and referring to adequate biological norms - centile charts. Arterial hypertension in children and adolescents may be primary, but much more often than in the adult population, it occurs secondary to diseases of other organs and systems. Early diagnosis of hypertension in the developmental age gives a chance to implement adequate therapy by treating the underlying disease, lifestyle modification or pharmacological treatment. The aim of effective therapy of hypertension is to prevent the occurrence of early and long-term complications of the disease, as well as to reduce the risk of hypertensive emergencies.